Learners Attitude and Academic Success Towards Science - Taghap, Raffy; Mannan Addani, Sitti Sheena (Journal of Education Culture and Society, 2024)
Aim. COVID-19 disrupted education, leading to new learning methods. Other factors like attitude are overlooked but can aid effective learning. This paper explores two major variables: the learners’ learning attitude and academic performance in science. The study analysed students’ learning attitude, academic performance, and relationships in a blended learning setting for science.Method. The study used a mixed-methods design, with both quantitative and qualitative phases. Participants were in a blended learning program.Results. Learning can happen in a blended learning modality, with the learners’ mean grade of 87.03 (Very Satisfactory). Learners have a favourable learning attitude towards science (3.49; moderate attitude). The highest aspect of the learning attitude of learners in the blended learning modality is affective (3.72; high attitude), followed by cognitive (3.62; moderate attitude) and behavioural (3.15; moderate attitude). Furthermore, there was a positive correlation, r(78) =.48, p < 0.01, between the LLATS and SAP of the learners in blended learning.Conclusion. Learning can effectively take place in a blended learning modality. Learners exhibit a positive attitude towards science learning in a blended learning environment, with affective attitudes ranking the highest, followed by cognitive and behavioural attitudes. This can be attributed to the teachers’ efforts in providing ample opportunities for the development of both affective and cognitive aspects of attitude. However, the pandemic has presented limitations in cultivating positive behaviour attitude. Learners persevered through challenges, thanks to dedicated teachers fostering positivity and academic growth.